FACTORES DETERMINANTES EN EL CUMPLIMIENTO DE ESQUEMA DE VACUNACIÓN EN PACIENTES PEDIATRICOS MENORES DE 1 AÑO CENTRO DE ATENCION PRIMARIA II LA TINGUIÑA – ICA 2021 - LEVANO MARALLANA, KAROLAY GRECIA (2021)
Introduction: Vaccination is a disease prevention process as is known to all, where the mother of the family plays an extremely important role based on her responsibility to comply in a timely manner with the vaccination scheme established by the health system and authorities. . Objective: To determine which are the factors that determine compliance with the vaccination scheme in pediatric patients under 1 year of age at the Primary Care Center II La Tinguiña - Ica 2021. Methodology: quantitative, descriptive, cross-sectional, not experimental. Results: Children <1 are between 2 and 4 months in 25% in each group, 50% of mothers with 25 to 30 years, 50% housewives, with secondary 50%, 67% with rented housing, 53% cohabiting. Factors in compliance with the vaccination scheme influence 75% of the population, only 25% do not influence. Internal factors influence 67%, do not influence 33%, while external factors influence 63% and do not influence 37%. 60% of the mothers report that the information in, 70% that the difficulty in access in 60%. The schedule becomes difficult in 60%, the interaction with the nurse in 80%, the long waiting time in 60% influences compliance. Conclusions: Internal and external factors are present in compliance with the vaccination scheme for children under 1 year of age. KEY WORDS: FACTORS, BREACH, VACCINATION, UNDER 1 YEAR, NURSE